PENERAPAN METODE MIND MAP UNTUK MENINGKATKAN PEMAHAMAN DAN HASIL BELAJAR MAHASISWA DALAM MATA KULIAH MANAJEMEN PEMASARAN DI IAIN PEKALONGAN - Misidawati, Dwi Novaria (LPPM STKIP PGRI Bandar Lampung, 2020)
This research is motivated by the low understanding and learning outcomes of students in the marketing management course. The purpose of this study was to improve student understanding and learning outcomes in marketing management courses using the mind map method at IAIN Pekalongan for the 2019/2020 Academic Year. This research was conducted on 50 students of class IIA of the Sharia Economics Study Program, consisting of 40 women and 10 men. The research method used was Classroom Action Research (PTK) using the PTK Kemmis & Taggart design consisting of 2 cycles, each consisting of planning, implementing, observing, and reflecting. Collecting data using observation instruments, tests, documentation, and questionnaires. The results of this study indicate an increase in understanding and learning outcomes in marketing management courses, marked by an increase in the number of students who reach the completeness limit, namely in cycle I there are 33 students (66%), in cycle II there are 44 students (88%). The conclusion of this study shows that the application of the mind map method can improve understanding and student learning outcomes in marketing management courses.